Knowledge and Actions Regarding Consumption of Instant Noodle in Elementary School Student Before and After the Provision of Educational Video - Novi Hardiyanti; Rina Maryanti; Verra Wulandary; Asep Rudi Irawan (ASEAN Journal of Science and Engineering Education, 2023)
Instant noodles are very popular with people of all ages as a popular food for the reason that noodles are delicious, practical and filling, especially for children. Apart from being delicious, instant noodles are also easy to find anywhere. The purpose of this study was to determine the extent of knowledge and actions of elementary school students regarding instant noodles, as well as to increase students' knowledge of instant noodles through educational video media. To support the research, we used qualitative research methods to students in elementary schools with data collection techniques used, namely giving pre-test and post-test using google form. The results showed that the average pre-test score was 26.15% and the average post-test score of students was 52.25%, which means an increase of 26.1%. Hence, students' knowledge of instant noodles can be increased by providing material through video media provided through the Whatsapp application.